Визначення внеску НТПВ у формування прибутку від реалізації продукції підприємства - Мазур, А. В. (Видавництво Львівської політехніки, 2015)
Досліджено питання фінансування стадії науково-технічної підготовки виробництва (НТПВ). Для забезпечення стадії НТПВ необхідними коштами запропоновано акумулювання власних коштів підприємства від реалізації науково-технічної продукції. Запропоновано використання частки прибутку від реалізації продукції для фінансування НТПВ. Розвинуто методичні засади визначення внеску НТПВ у формування прибутку підприємства. Proceedings of scientific and technical preparation of production requires certain costs, as it requires the use of machines, equipment, technologies with high technical and economic indicators. Financing of STPP is a prerequisite in order to achieve the desired result, and, accordingly, production of a certain product (development). The article examines problem of financing the stage of scientific and technical preparation of production (STPP). The funds needed to finance the STPP stage, can be obtained by direct sale of products of STPP. Another way for the STPP products realization is the implementation of the design and technological documentation, scientific and technological working in own production. In most cases, the results of the stage of STPP are directly introduced into the production of new or improved products. In that case it is not about direct result of the final working of STPP. However, the activity of this stage significantly affects the overall performance of the enterprise. It is therefore possible to determine the result of the stage of STPP as a share of the profit of the enterprise. It this case this part of the profits can be used to finance the STPP stage in process of its redistribution, which enables to conduct new research and development of the enterprise or to upgrade existing technology. In order to determine the profits of the stage of scientific and technical preparation of production as a share of scientific-research complex of work in the final result of the enterprise it is proposed to reflect partial profits of STPP considering income from sales of the enterprise and the coefficient of contribution to the forming the STPP profits. The coefficient of contribution to the forming the STPP profits of the enterprise is proposed determine by taking into account a number of factors that impact on the financial performance of the enterprise on the stage of STPP. The composition of such factors should be investigated and form for the resource and process approach. From the standpoint of resource-procession approach is obvious that to determine the STPP contribution to the forming of financial results of the company, it is necessary to determine the share of the scientific and technical operations deposit in the production. It is appropriate to define the deposit of the stage of STPP, if the product that is produced now are innovative, modernized or characterized by improved technical and economic parameters in comparison with a product that was made in previous periods, or analogs on the market. Accordingly to determine the contribution of scientific and technical works that provide innovation or modernization of the product, it is necessary to identify the contribution of innovative work in total work performed during production. Consequently, it is proposed to determine the coefficient of contribution to the forming the STPP profits of the enterprise on the basis of partial indicators that reflect the impact of relevant factors. The own funds from scientific and technical products sales accumulation is offered in order to provide the necessary funds. The use of share of profits of products realization to finance STPP is offered. Methodical bases of determining of the STPP contribution to the profits forming are developed.
Determination of the STPP deposit in forming the profit of enterprise
Keywords: науково-технічна підготовка виробництва (НТПВ); фінансування НТПВ; внесок НТПВ у формування прибутку; scientific and technical preparation of production (STPP); financing the STPP; STPP contribution to the profit forming